Biodegradation of naphthalene by bacteria isolated from petroleum contaminated soil - M.F, Tawfiq,; A.R, Abdullah,; A.F, Merican, (Malaysian Journal of Science, 2001)
Environmental isolates of Pseudomonas sp., Aeromanas sp. and Acinetobacter sp. were tested for their ability to grow and degrade naphthalene in liquid culture media. The experiments were carried out during 62 h incubation time, in which the three bacteria were incubated separately. Viable cell determination using plate count method showed that the bacteria grew well in media containing naphthalene at different concentrations. Residual naphthalene was quantified by GC-MS employing anthracene as internal standard. All bacteria were found to significantly removed naphthalene from the culture media. Bacterial growth was enhanced in the presence of naphthalene in the media. Acinetobacter sp. was able to remove 68 %Â·of the naphthalene in the culture media during 62 h of incubation time.